Diksi Dan Gaya Bahasa Pada Cerkak Sindhen Karya Andjar Any Kajian Stilistika - Hasan, Imadul Bilad; Sulanjari, Bambang (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2022)
The purpose of this paper is to find out the style of language and diction in the Sindhen story by Andjar Any. Cerkak is one of the literary works that is included in the type of prose literary work. The absolute characteristic in literary works is the beauty, authenticity and artistic value in its content and expression. A work cannot be said to be a literary work if one of these elements is not fulfilled. Cerkak is similar to short stories or short stories, because cerkak is an abbreviation of